2017
DOI: 10.1103/physrevlett.118.221101
|View full text |Cite|
|
Sign up to set email alerts
|

GW170104: Observation of a 50-Solar-Mass Binary Black Hole Coalescence at Redshift 0.2

Abstract: We describe the observation of GW170104, a gravitational-wave signal produced by the coalescence of a pair of stellar-mass black holes. The signal was measured on January 4, 2017 at 10∶11:58.6 UTC by the twin advanced detectors of the Laser Interferometer Gravitational-Wave Observatory during their second observing run, with a network signal-to-noise ratio of 13 and a false alarm rate less than 1 in 70 000 years. −0.07 . We constrain the magnitude of modifications to the gravitational-wave dispersion relation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

49
1,874
6
15

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,319 publications
(1,944 citation statements)
references
References 164 publications
49
1,874
6
15
Order By: Relevance
“…The recent observation GW170104 [6] disfavors the aligned-spin configuration. Motivated by this measurement, the first group is concerned with BBHs with antialigned spins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent observation GW170104 [6] disfavors the aligned-spin configuration. Motivated by this measurement, the first group is concerned with BBHs with antialigned spins.…”
Section: Resultsmentioning
confidence: 99%
“…The BBH waveform models have been further improved over the years and many applications to detection have already followed. In the context of testing the dynamical sector of general relativity (GR) [45], for instance, GW150914, GW151226 and GW170104 showed no statistical significant evidence on deviations from PN coefficients of the GW phase predicted by GR [5,6,45]. In [46], GW150914 was directly compared with NR simulations and it was shown that they are mutually consistent.…”
Section: Goals and Motivationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations of black holes are undergoing a revolution, with the advent of gravitational wave astronomy [2][3][4][5] and the promise of very-longbaseline radio observations of supermassive black holes by the Event Horizon Telescope [6,7]. While black holes are consistent with all electromagnetic and gravitational wave observations to date [4,5,[8][9][10], no experiment has been able probe spacetime near the event horizon [11][12][13]. Moreover, the event horizon is at the heart of the BH information paradox [14], and the role of black holes in a quantum theory of gravity is an open question.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the LIGO Scientific Collaboration and Virgo Collaboration, based on data acquired by the Advanced LIGO [2] and Advanced Virgo [3] detectors, have announced detections of gravitational waves from coalescing stellar mass black hole binaries [4][5][6][7][8][9] and a neutron star binary [10]. This opened up the era of gravitational wave astronomy.…”
Section: Introductionmentioning
confidence: 99%